Motivasi Petani dalam Membudidayakan Tanaman Pepaya Calina (Carica papaya L) (Kasus Kelompok Tani Pepaya Calina di Desa Sulangai, Kecamatan Petang, Kabupaten Badung) - WIWEKA, DEWA PUTU GEDE SATRIA; SUARDI, I DEWA PUTU OKA; DJELANTIK, A.A.A WULANDIRA SAWITRI (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism); Vol.7, No.3, Juli 2018, 2018)
The Farmer’s Motivation In Cultivating The Papaya Calina Plant (Carica papaya L) (The Farmer’s Group of Calina Papaya at Sulangai Village, on Petang District, in Badung Regency). Sulangai village is the village where most of the villagers work as a farmer. One of the farmer’s work done by the farmer in that village is papaya calina. Based on the description above, it’s interesting to analyze about the motivation faced by the farmer in cultivating the papaya calina plant at Sulangai village, on Petang district, in Badung regency. The purpose of this research is to know the farmer’s motivation in cultivating the papaya calina plant at Sulangai village, on Petang district, in Badung regency. The research held at sulangai village, on Petang district, in Badung regency particularly in farmer’s group of papaya calina. The location of the research is based on the purposive method which is determination of the research location deliberately. The population in this research is 20 farmers. Based on the research data, the intrinsic motivation of the farmer cultivating the papaya calina plant at Sulangai village, on Petang district, in Badung regency is categories high percentage about 70,81%. The intrinsic motivation of the farmer in cultivating the papaya calina plant generally categories in high percentage about 79,09%.Based on the research the farmer’s group as the one who does this job is brave to try this technology in cultivating the papaya calina plant which is given by the instructor. By trying the technology, the farmer’s group will get more new experiences to do in cultivating papaya calina in the future.